Nepeta angustifolia C. Y. Wu improves renal injury in HFD/STZ-induced diabetic nephropathy and inhibits oxidative stress-induced apoptosis of mesangial cells. (12th June 2020) - Huang, Shan; Tan, Meng; Guo, Feng; Dong, Linsha; Liu, Zhiming; Yuan, Ruiying; Dongzhi, Zhuoma; Lee, Dong-Sung; Wang, Yuefei; Li, Bin
Abstract: Ethnopharmacological relevance: As an important medicinal material constituting a variety of traditional Chinese medicine prescriptions, Nepeta angustifolia C. Y. Wu was used as a folk medicine to treat various vascular-related diseases including apoplexia, and cerebral haemorrhage in Tibet, China. Our previous studies have shown that this plant had a significant protective effect on vascular dysfunction of the intracerebral haemorrhage and diabetic rats. In present study, we aimed to investigate the protective effects and underlying mechanisms of Nepeta angustifolia on diabetic nephropathy (DN), a microvascular complication. Aim of the study: This study is aim to evaluate the protective effect of ethanol extracts of N. angustifolia (NA) on DN, and explore mechanism of action to provide basis for its pharmacological action against DN. Materials and methods: High-fat diet and low-dose streptozotocin administration (HFD/STZ) induced diabetic rats were randomly divided into 5 groups (n = 8): the diabetic model group, metformin group, and three dose groups of NA (60 mg/kg, 120 mg/kg, 240 mg/kg). After administration of NA for 8 weeks, the blood, urine and renal tissue were collected for subsequent experiments. Biochemical markers (urine protein, Cr, BUN), oxidative stress makers (SOD, GSH-px and MDA) and pro-inflammatory mediators (TNF-α, IL-1β, IL-6 and MCP-1) were evaluated by commercial kit and ELISA, respectively. The effect of NA on DN was further confirmed by evaluation of renal histopathology by using the H&E, PAS and Masson staining. The H2 O2 -induced HBZY-1 cells (rat glomerular mesangial cells) were also been used to evaluate the renal protective effect of NA (50 μg/mL, 100 μg/mL, 200 μg/mL). The oxidative stress makers were detected by commercial kit. The levels of apoptosis and related proteins (caspase 3, 9) were detected by TUNEL assay and western blot analysis, respectively. The depolarization of mitochondrial membrane potential was detected by JC-1 staining assay. Results: The administration of NA is helpful to maintain near normal body weight, blood glucose, urine volume, urine protein, kidney index and serum levels of Cr and BUN. NA treatment significantly improve renal dysfunction by the down-regulation of renal oxidative stress and pro-inflammatory mediators in HFD/STZ induced diabetic rats. In vitro experiments, NA has a significant cellular protective effect in H2 O2 -induced HBZY-1 cells, as well as the regulation in increases of SOD level and the decreases of ROS and MDA levels. Furthermore, NA treatment can significantly inhibit H2 O2 induced mesangial cells apoptosis by the increasing mitochondrial potential and suppressing caspases-madiated signaling pathway. Conclusions: NA has obvious improvement on renal dysfunction in HFD/STZ induced diabetic rats. NA can protect mesangial cells by inhibiting oxidative stress induced apoptosis, which may be related to its regulation of mitochondrial-caspase apoptosis pathway. Graphical abstract: Image 1